Define a good prognosis of RNF43 codon 659-mutated and concomitant genomic signatures in CRC: an analysis of the cBioPortal database - Wang, Feng; Lin, Li; Li, Zhongkang; Qin, Lei; Zhang, Shuai; Hu, Xueqing; Zhao, Yunbo; Huang, Yingying (Frontiers in Oncology, 2025)
BackgroundHeterogeneity of colorectal cancer (CRC) leads to significant differences in Overall Survival (OS). RNF43 is a new predictive marker for prognosis and anti-BRAF/EGFR combinatory therapies of CRC recently. However, few studies focused on the relationship between RNF43 and co-mutation characteristics and prognosis. This study aims to explore the different prognostic subtypes of RNF43-mutated CRC by analyzing the association of clinicopathological and genomic characteristics with survival outcomes.MethodsThe clinical characteristics, mutational characteristics, and survival data of CRC patients were obtained for RNF43-mutated analysis from cBioPortal. All mutation data were filtered by the 1021-panel (Geneplus-Beijing, China), and the processed data were used to analyze the predictive value of RNF43-mutated to OS and concomitant co-mutations. Cox regression analysis was selected to explore prognostic biomarkers, and finally, BRAF and MSI were selected for subgroup analysis. The independent validation cohort comprised 339 cases of stage IV CRC from Beijing Hospital.Results11 datasets with 4028 patient data were screened for this study. The most common variant was frameshift, which occurred in codon 659-mutated of exon 9, including RNF43 p.G659Vfs*41 (N=116) and RNF43 p.G659Sfs*87 (N=2). RNF43 codon 659-mutated occurred frequently in right-sided CRC (59.32%, N=70, P<0.0001), and rarely in the left-sided (11.02%, N=13). The incidence of TMB-H in the RNF43 codon 659-mutated group was 93.22% (110/118), and MSI-H was 78.81% (93/118). Univariate Cox analysis and multivariate Cox analysis showed that MSI-H was the most significantly different biomarker for better prognosis (P=0.004, HR=3, CI 1.4-6.4), and Class 1 BRAF V600E was the most different biomarker for worse prognosis (P<0.001, HR=0.3, CI 0.21-0.42). RNF43 codon 659-mutated with non-class 1 BRAF-mutated or MSI-H suggests a better prognosis in CRC. We found that G1 (RNF43 codon 659-mutated, non-class 1 BRAF-mutated, and MSl-H) had a better PFS and OS. The mutation difference analysis showed that the core genes related to the cancer signaling pathway (PI3K-Akt signaling pathway, MicroRNAs pathway, DNA damage repair, and tumor suppressor genes) were highly frequent in G1. The analysis comparing the core gene mutation difference between RNF43-mutated and wild-type in the validation cohort yielded consistent conclusions.ConclusionsIn CRC, we found that the G1 cohort had the best prognosis, and patients with RNF43 Non-codon 659-mutated, BRAF V600E and MSS had the worst prognosis. This may provide clinical value for patients’ further accurate prognosis prediction, curative effect prediction, and follow-up management of patients.